Temporal profile of replication of human chromosomes - Jeon, Yesu (National Academy of Sciences, 2005)
Chromosomes in human cancer cells are expected to initiate replication from predictably localized origins, firing reproducibly at discrete times in S phase. Replication products obtained from HeLa cells at different stages of S phase were hybridized to cDNA and genome tiling oligonucleotide microarrays to determine the temporal profile of replication of human chromosomes on a genome-wide scale. About 1,000 genes and chromosomal segments were identified as sites containing efficient origins that fire reproducibly. Early replication was correlated with high gene density. An acute transition of gene density from early to late replicating areas suggests that discrete chromatin states dictate early versus late replication. Surprisingly, at least 60% of the interrogated chromosomal segments replicate equally in all quarters of S phase, suggesting that large stretches of chromosomes are replicated by inefficient, variably located and asynchronous origins and forks, producing a pan-S phase pattern of replication. Thus, at least for aneuploid cancer cells, a typical discrete time of replication in S phase is not seen for large segments of the chromosomes.